REVIEW: PLANTS WITH REPELLENT ACTIVITY - Purnama, Uwan; Faramayuda, Fahrauk (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Mosquitoes are vectors of illnesses, such as encephalitis, dengue, filariasis, intestinal sickness, and encephalitis. These diseases have become epidemics in Indonesia and around the world. Natural repellents are alternatives for preventing mosquito-borne diseases that are safe, easily degradable, and eco-friendly. This review aimed to identify compounds in plants with mosquito repellent activity. Data were obtained from national and international journals using search platforms, including PubMed, Scholar, SciDirect, and Hindawi. This review focuses on plants with repellent activity, their resulting repellent activity, the content of bioactive compounds, and the mosquito species used. Many plants contain naturally occurring compounds that can repel mosquitoes. Following scientific research, 14 bioactive compounds have been shown to have repellent activity in plants. Keywords: repellent, volatile oil, mosquitos, bioactive compounds, narrative literature review